Own experience of surgical treatment for advanced cancer of the tongue and the mouth floor - P. V. Svetitskiy; I. V. Pustovaya; M. A. Engibaryan; M. V. Bauzhadze; A. K. Donskaya (Южно-Российский онкологический журнал, 2022)
Purpose of the study. Improvement of surgical treatment outcomes in patients with advanced cancer of the tongue and the mouth floor providing radical surgery with preservation of the organ functions.Materials and methods. Two patients with advanced cancer of the tongue and the mouth floor with metastases to lymph nodes in the neck (St.4 (IVA, рT4a N2b M0), clinical group 2, were operated on according to our special technique. The surgery was performed under endotracheal anesthesia. After cervical lymph node dissection, the tongue and the mouth floor tissues were resected intraorally. The incisions were made through their entire thickness along healthy tissues. Smears were taken from the dissected tissues for intraoperative pathology consultation control for the presence of cancer cells. The tissues of the mouth floor affected by the tumor were completely removed without going beyond the hyoglossus muscle, since the lingual and hypoglossal nerves go along its outer surface. This allowed radical tumor removal with preservation of the tongue functions.Results. Patients operated on according to our special technique have been observed for more than 9 months without continued tumor growth and recurrences tumor with preservation of the tongue and the mouth floor functions.Conclusion. In such patients, ablastics principles are combined with the preservation of the tongue functions. This can be achieved because after removal of the tongue tumor, resection of the mouth floor is performed without going beyond the hyoglossus muscle not affected by the tumor, since the lingual and hypoglossal nerves go along its outer surface. Complying with ablastics, it preserves the tongue functions: chewing, swallowing, articulate speech, taste perception.